THE GENERATE OF E-MODULES BASED ON CONTEXTUAL ON HARMONIOUS MOTION MATERIALS TO OPTIMIZE THE UNDERSTANDING CONCEPT IN SMA NEGERI 10 MEDAN - Nainggolan, Raivita Jesica; Bukit, Nurdin (IPER (Indonesian Physics Education Research), 2023)
This study aims to knowing the validity, practicality, effectiveness, and optimization of students' understanding of concepts after using e-modules based on contextual on harmonious motion materials. The subjects in this research were students of class X MIA 1 & X MIA 2 in SMA Negeri 10 Medan. This type of research is Research and Development (R&D) using a 4D model. The data collection instruments is consisted of validation questionnaires, teacher and students response questionnaires as well as pretests and posttests of concept understanding abilities. The data analysis techniques are quantitative and qualitative. The results of this study gets very valid criteria with an average score of material experts getting 92.96%, and media experts getting 93.40%, learning experts at 96.48%, the teacher's response with 94.79% and 95.02% student response included in the practical criteria, the effectiveness with an n-gain of 0.71 in the high category, and the understanding of students' concepts by the hypothesis of the calculation tcount is 2,364 while the ttable is 1,799, it was stated that Ha was accepted. So it can be concluded that e-modules based on contextual on harmonious motion materials are valid, practical, effective, and can optimize the understanding of student concepts